Identification of microcalcification in mammographic images / Noor Azliza Abdul Shauti - Abdul Shauti, Noor Azliza (2008)
This study is conducted to determine the minimum detectable microcaicifications sizes for mammography identification. Microcalcification is sometimes difficult to detect because of their small size and low contrast. Identification microcaicifications images application was developed to improve detection of microcaicifications efficiency in image quality and high detection efficiency in early detection environments. This identification. application was developed to overcome the limitations of conventional mammography the currently identification. Beside that, this study will apply the algorithm experimental analysis such as invert, contrast, blur, and sharpen in analyzing the enhancement. The result also will be compare with all of algorithm experimental. This study will focused on mammographic images only by using mammography CAD (computer-aided diagnosis). By using this identification, it can simulate in flexible images post processing and analysis in easy image management using Java aplication. The mammographic images quality can be high, clear, efficiency and flexible. From the result showed that image enhancement is to give a good and better image after ehnace.For future direction, this enhancement can be use to improve a quality of image and in image processing field especially in identify of microcalcification in future.